Investigation and Evaluation of Organic Chemistry of Alpha-Glucosidase Inhibitors for Managing Blood Sugar Levels - Ali Shah, Syed Muazzam; Akram, Farzana; Naeem, Hajra; Fatima, Rida; Murtza, Muhammad; Aslam, Muhammad Shakeel; Attiq Ur Rehman; Aamir, Muhammad (Indus Journal of Bioscience Research, 2025)
Diabetes, particularly Type 2 diabetes, is a chronic metabolic disorder characterized by insulin resistance and impaired glucose metabolism. One promising approach to managing blood glucose levels in diabetic patients is the use of alpha-glucosidase inhibitors (AGIs), which work by delaying the digestion and absorption of carbohydrates in the small intestine. This research paper explores the organic chemistry behind alpha-glucosidase inhibitors, focusing on their mechanism of action, structure-activity relationship (SAR), synthetic strategies, and the development of more selective and potent compounds. Furthermore, we discuss the therapeutic potential of AGIs in managing blood sugar levels and mitigating the long-term complications of diabetes.